If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9y+3y-17=43
We move all terms to the left:
9y+3y-17-(43)=0
We add all the numbers together, and all the variables
12y-60=0
We move all terms containing y to the left, all other terms to the right
12y=60
y=60/12
y=5
| 2(x+7)-6x=-26 | | 0x+7=2x+1 | | x+38=4x–31 | | 7v+3v=40 | | a+38=4a–31 | | 4/3c=c+2 | | 98x-13x=-4 | | 4/y=13/11 | | 12x+15x=16 | | 5x-(4-2x)=-(×+11)-1 | | 25=-2+9(x+3) | | 6x-98=128 | | 4(3+w)-w=6+3(w+2 | | x+54=5x+26 | | (6x-98)=128 | | 52x=x81 | | 12x+12=4x+60 | | 52x=81 | | 52xx=81 | | 8x-4x=6 | | x+9+84+x+51=180 | | y+1/8=6/8 | | 2(w-2)-5w=14 | | 3(3x-12)=6(2x-4) | | 3(2t-5)=20-2t | | 6x+20=3x-15 | | 3w+14=4w-1 | | 2x+5+80=3x-14 | | 0.2x-3.2/5=1.8 | | 17z-2=20z-17 | | `12-9x=-3(x+10) | | (3(x+1))/4-(2x-1)/3=-x/3+(3(2x-1))/4 |